Hydrolysis of Vegetable Raw Pectin-Containing Materials Under Vibration and Centrifugal Mixing of Liquid Environment - Palamarchuk, Igor; Palamarchuk, Vladyslav; Gudzenko, Maxim; Sarana, Viktor; Mukoid, Roman (My University, 2021)
Transformation of various plant origin products with the use of heat and mass processes is one of the most common processes in the food industry. The problem of removing solid particles of inhomogeneous liquid systems outside the zone of intensive mass transfer in the industry is solved by various means, among which we can note the use of ultrasound, centrifugal forces, low-frequency oscillations. Among the multifaceted mechanical action methods on various dispersed systems in heat and mass transfer processes, vibration plays an important role. It is one of the most effective means for forming and correcting the desired state of inhomogeneous media. Creating a field with vibration action on various technological environments significantly activates and streamlines heat and mass transfer processes, improves the quality of various processes of mixing materials with properties that do not match each other, and reduces the duration of operating cycles and energy consumption. When creating a combined force and moment imbalance, both the dynamic loads on the support nodes increase, and there is a more intense oscillating movement of the blade shaft along its axis. At momentary imbalance, the loads on the support nodes are reduced while providing the desired linear oscillating motion, which is quite effective for the system under study. With the help of software and methods of mathematical and statistical analysis, graph-analytical power ratios, kinetic-energy parameters of the designed symmetry were built, which allowed substantiating energy-efficient modes of operation of the developed device.
Keywords: кафедра біотехнології продуктів бродіння і виноробства; unbalance elements; oscillating system; imbalance; vibrational mixing; vibration exciter; дебалансні елементи; коливальна система; дисбаланс; вібраційне перемішування; віброзбудник